The Impact of Digitalization on Efficiency of Procurement Function in Organizations: A Case Study of Jumia Uganda - Kevin Wamani Isingoma (Uganda Christian University, 2024)
This study examined the impact of digitalization on the efficiency of procurement functions, Jumia as the case study. The research analyzed how digital tolls and systems were integrated into the procurement process and evaluated their importance in increasing procurement efficiency, cost effectiveness, and overall organizational performance. The study also discussed the problems faced by Jumia in adopting and implementing digital procurement solutions. The research adopted quantitative research approach, using questionnaires to collect data from members if Jumia Uganda. The data was analyzed to identify patterns and develop conclusions about the influence of digital procurement on the organization’s efficiency and performance. The findings showed that digital procurement technologies greatly streamlined procurement procedures, promoted faster decision-making, improved accuracy, and increased supplier relationship management. Never the less, problems such poor internet infrastructure, high capital required, resistance to change, and data insecurity problems were noted as challenges to effective digital procurement adoption. The research also showed that as digitization had a positive influence on procurement efficiency at Jumia, solving the identified problems was important for realizing the benefits of digital procurement. Recommendations include improving infrastructure, cutting costs, enhancing data security, and implementing change management training. This study contributed to the understanding of digital procurement's role in today’s procurement functions and gives insights to companies aiming to boost their procurement efficiency the digitalization.
undergraduate Research